Lactic acid bacteria’s isolation and probiotic properties from "Nem chua", traditional fermented pork - NGUYEN TRUNG TRUC; QUACH VAN CAO THI; DINH THI KIM NHUNG; TRAN QUANG MINH HIEU; LE VAN UT; KHOA DANG DANG (Biodiversitas Journal of Biological Diversity, 2026)
Nem chua, a renowed traditional Vietnamese fermented pork product, is consumed without heat treatment, thereby posing a potential risk of contamination with pathogenic microorganisms. This investigation concentrated on isolation and characterization lactic acid bacteria (LAB) with potential probiotic properties. In parallel, Staphylococcus spp.-a pathogenic group commonly associated with foodborne infections in Nem chua-were also isolated and identified. A total of twenty-one LAB isolates were isolated on MRS (de Man, Rogosa, and Sharpe) medium supplemented with calcium carbonate (CaCO₃), while six Staphylococcus spp. strains were obtained on MacConkey medium from Nem chua samples. Probiotic evaluation revealed that all LAB strains produced inhibition zones ranging from 0.63 to 1.56 cm in diameter, as determined by the agar well diffusion method. The acid tolerance of the five LAB strains with the strongest antibacterial activity was assessed, with strain L2 exhibiting the highest ΔOD₆₀₀ at pH 3.0 after 9 hours of incubation. For bile salt tolerance, three LAB strains were able to grow at 0.30% bile salt, whereas only strain L2 tolerated 1% concentration. Antibiotic susceptibility testing indicated that 42.1% of LAB strains were sensitive to doxyicycline, whereas resistance to streptomycin, ciprofloxacin, levofloxacin, and vancomycin were observed in all strains. Furthermore, all LAB strains produced amylase and cellulase, but only three strains (L2, L8, and L16) exhibited extracellular protease activity. Molecular identification based on 16S rRNA sequencing confirmed that strains L2, L8, and L16 corresponded to Lactobacillus plantarum, L. farciminis, and Lactiplantibacillus argentoratensis, respectively. These findings underscore the potential application of the isolated LAB isolates for enhancing the safety and quality of traditional Nem chua. The identified strains may be progress associated as utilitarian starter social orders to advance microbial security, material characteristics, and by and expansive quality consistency in customary developed meat era.